Is surgery superior for distal ulna fractures? a comprehensive systematic review and meta-analysis - Zakaria Chabihi; Brahim Demnati; Mohamed Moussadiq; Tariq Aalil; Yassine Fath El Khir; El Mehdi Boumediane; Mohamed Amine Benhima; Imad Abkari (Journal of Orthopaedic Surgery and Research)
Abstract Background The management of distal ulna fractures remains a subject of considerable debate within orthopedic practice. This systematic review and meta-analysis aims to evaluate the efficacy of surgical versus non-surgical management strategies for distal ulna fractures and their impact on functional outcomes. Methods This study followed PRISMA guidelines and involved a systematic search of databases like PubMed, Scopus, and Web of Science for relevant studies published in English up to December 2023. The search included keywords such as “ulnar styloid fracture”, “non-surgical management”, “surgical management”, and “treatment outcomes”. Studies were selected based on predefined inclusion and exclusion criteria, and data were extracted on patient demographics, fracture characteristics, treatment details, functional outcomes, patient-reported outcomes, complications, and follow-up duration. The methodological quality of included studies was assessed using the GRADE system. The meta-analysis used standardized mean differences for continuous outcomes and log odds ratios for dichotomous outcomes. Results The initial search yielded 1253 studies, which were narrowed down to 12 studies suitable for review after removing duplicates and irrelevant articles. These studies included a total of 709 patients, with 422 receiving non-surgical management and 287 undergoing surgical treatment. The results showed no significant differences in grip strength, DASH score, or VAS score between surgical and non-surgical management. However, a higher union rate was observed with surgical management. Limitations The moderate quality of the included studies and the moderate to high heterogeneity among them are noted as limitations, indicating a need for more standardized research methodologies in this area. Conclusions While surgical management may offer a higher union rate, the choice of treatment should be individualized, balancing the potential benefits against the risks of surgery, as ORIF implants are typically associated with higher ulnar-sided pain rates and limited ulnar deviation due to implant prominence. Future research should focus on standardizing study designs to improve the quality of evidence in the management of distal ulna fractures. Level of evidence I Evidence from a meta-analysis and systematic review from all relevant studies.